TYPES OF EXTRACELLULAR ENZYMES SECRETED BY FUNGI - Badr, Sanaa Qasem (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to review the diversity and significance of extracellular enzymes secreted by fungi, with a focus on their ecological functions and industrial applications. Method: A literature-based analysis was conducted, summarizing the main categories of fungal enzymes, including cellulases, ligninases, proteases, lipases, and pectinases, as well as their associated roles in both natural and applied contexts. Results: The findings highlight that fungal extracellular enzymes play essential roles in breaking down complex organic materials, thereby facilitating nutrient cycling, decomposition, and ecosystem balance. Industrially, these enzymes are widely applied in biofuel production, bioremediation, food processing, pharmaceuticals, and textiles, demonstrating their versatility and economic value. Novelty: This review integrates ecological and industrial perspectives, emphasizing the dual importance of fungal enzymes as natural mediators of biodegradation and as key biocatalysts driving sustainable innovations in biotechnology and environmental management.